Bipolar secondary battery and method of manufacturing the same

CN122996526APending Publication Date: 2026-10-27LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202680002916.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-09-22
Filing Date
2026-01-26
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0008]然而,双极二次电池通常具有这样的缺点:当在堆叠了多个单元电池的状态下注入或浸渍电解质时,电解质可能在单元电池之间泄漏或泄漏到双极二次电池的外部,从而导致短路

Benefits of technology

[0025]根据一个实施方案的双极二次电池应用形成在相互相邻的双极电极和分隔件上的凝胶电解质,而不是液体电解质,从而有效地抑制电解质的泄漏,并使得能够应用简化的密封结构。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996526A_ABST
    Figure CN122996526A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a bipolar secondary battery including a gel electrolyte and thus exhibiting excellent life characteristics and low resistance while suppressing leakage of the electrolyte, and a manufacturing method thereof. The bipolar secondary battery is characterized in that: bipolar electrodes in which negative electrode active material layers and positive electrode active material layers are formed on both surfaces of a metal current collector are stacked in plural, the positive electrode active material layer and the negative electrode active material layer of bipolar electrodes adjacent to each other face each other with a separator interposed therebetween, one or more of the separator, the positive electrode active material layer, and the negative electrode active material layer are impregnated with a gel electrolyte, and the gel electrolyte is formed in an excess volume larger than the total pore volume of the separator, the positive electrode active material layer, and the negative electrode active material layer in a state in which the gel electrolyte is not impregnated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Cross-reference to related applications

[0002] This application claims priority and benefit to Korean Patent Application No. 10-2025-0025906, filed on February 27, 2025, and Korean Patent Application No. 10-2025-0136349, filed on September 22, 2025, the entire contents of which are incorporated herein by reference.

[0003] This disclosure relates to a bipolar secondary battery and a method for manufacturing the same, the bipolar secondary battery comprising a gel electrolyte, and thus exhibiting excellent lifetime characteristics and low resistance while suppressing electrolyte leakage. Background Technology

[0004] Recently, as the application of lithium secondary batteries has rapidly expanded not only to supply power to electronic devices (such as electrical equipment, electronic devices, communication equipment, and computers), but also to store and supply power to large-area devices (such as automobiles and power storage systems), the demand for secondary batteries with high capacity, high output, and high stability is increasing.

[0005] Conventional lithium-ion secondary batteries typically have a structure in which multiple cell units are connected in parallel, and each cell unit has a structure including a single positive electrode and a single negative electrode, each coated with an active material of the same polarity on a current collector, and a separator or electrolyte layer inserted between the single positive and single negative electrodes. In such a conventional battery structure, from the perspective of the current flow path, the resistance increases, the power density decreases, and problems such as high heat generation and low safety may occur.

[0006] Therefore, interest and research on bipolar secondary batteries have increased significantly recently. Bipolar secondary batteries can have a structure in which a plurality of bipolar electrodes, each coated with an active material of different polarities on two surfaces of a current collector, are stacked, and spacers and / or electrolytes are inserted between adjacent bipolar electrodes.

[0007] A bipolar secondary battery has a structure in which individual cells are connected in series, defined by positive and negative electrodes facing each other and a separator inserted between the positive and negative electrodes. Therefore, a bipolar secondary battery can shorten the current flow path, which reduces resistance and increases power density, and simplifies the components and structure used to control the individual cells within a module or group including a bipolar secondary battery.

[0008] However, bipolar secondary batteries typically have the following drawback: when injecting or impregnating electrolyte in a stacked configuration of multiple cells, the electrolyte may leak between the cells or to the outside of the bipolar secondary battery, leading to a short circuit. Therefore, conventional bipolar secondary batteries inevitably require complex sealing and encapsulation structures to suppress electrolyte leakage between cells and to prevent electrolyte leakage to the outside of the battery.

[0009] Introducing such a complex sealing and encapsulation structure not only complicates the manufacturing process and structure of bipolar secondary batteries, but also often fails to completely prevent electrolyte leakage despite the introduction of such a sealing structure. This has become one of the main technical drawbacks hindering the practical application of bipolar secondary batteries.

[0010] To address these drawbacks, attempts have been made to apply all-solid-state cell technology, including a solid electrolyte layer, to bipolar secondary batteries, or to use gel electrolytes instead of liquid electrolytes. However, all-solid-state cell technology still suffers from limitations that make practical implementation difficult, such as poor interfacial properties between the electrodes and the solid electrolyte layer, and low ion conductivity.

[0011] In addition, bipolar secondary batteries using gel electrolytes also have the following drawbacks: not only are the interfacial characteristics between the gel electrolyte and each electrode insufficient, making it difficult to achieve excellent ion conductivity and low resistance, but also the electrochemical characteristics of the bipolar secondary battery deteriorate as the electrolyte contained in the gel electrolyte volatilizes or is consumed during battery use, and the lifespan of the bipolar secondary battery is insufficient. Summary of the Invention

[0012] Technical issues

[0013] Therefore, one object of this disclosure is to provide a bipolar secondary battery and a method for manufacturing the same, the bipolar secondary battery comprising a gel electrolyte, and thus exhibiting excellent lifetime characteristics and low resistance while suppressing electrolyte leakage.

[0014] Technical solution

[0015] According to one aspect of this disclosure, a bipolar secondary battery is provided, characterized in that: bipolar electrodes, wherein a negative electrode active material layer and a positive electrode active material layer are respectively formed on two surfaces of a metal current collector, are stacked in a plurality of layers; the positive and negative electrode active material layers of adjacent bipolar electrodes face each other with a spacer inserted between them; one or more of the spacer, the positive electrode active layer, and the negative electrode active layer are impregnated with a gel electrolyte; and

[0016] Based on the total pore volume of the separator, positive electrode active material layer, and negative electrode active material layer in the unimpregnated state, the gel electrolyte is formed at a volume corresponding to 103% to 200%.

[0017] In a bipolar secondary battery according to one embodiment, the gel electrolyte may include: a first gel electrolyte impregnated in one or more of a separator, a positive electrode active material layer, and a negative electrode active material layer, and a second gel electrolyte further formed between the positive electrode active material layer or the negative electrode active material layer facing each other and the separator. Such a first gel electrolyte and a second gel electrolyte may be formed, for example, from the same composition, and may be formed continuously under conditions of mutual coupling.

[0018] In a more specific embodiment, the total thickness of the second gel electrolyte further formed between the positive electrode active material layer or the negative electrode active material layer and the separator can be from 0.1 μm to 20 μm.

[0019] In a more specific embodiment, the first gel electrolyte may be impregnated into all of the separator, the positive electrode active material layer, and the negative electrode active material layer.

[0020] In addition, the second gel electrolyte can be formed between the separator and the positive electrode active material layer, and between the separator and the negative electrode active material layer, respectively.

[0021] In this case, based on the total pore volume of the separator, the positive electrode active material layer, and the negative electrode active material layer in the state without being impregnated with the gel electrolyte, the second gel electrolyte can be further formed between the separator and the positive electrode active material layer, or between the separator and the negative electrode active material layer, corresponding to a volume of 2% to 60%.

[0022] In this way, the thickness of the second gel electrolyte further formed between the separator and the positive electrode active material layer and / or between the separator and the negative electrode active material layer can be from 0.05 μm to 20 μm.

[0023] Meanwhile, according to another aspect of this disclosure, a method for manufacturing a bipolar secondary battery according to one embodiment is provided. The manufacturing method according to this other aspect includes: a first step of forming a negative electrode active material layer and a positive electrode active material layer on two surfaces of a metal current collector, respectively, to manufacture a bipolar electrode; a second step of coating or curing a composition comprising a curable multifunctional compound and an electrolyte forming a gel electrolyte onto the negative electrode active material layer or the positive electrode active material layer; a third step of coating the gel electrolyte forming composition onto at least one surface of a separator and curing it; and a fourth step of stacking the bipolar electrodes in a plurality of stacks such that the positive and negative electrode active material layers of adjacent bipolar electrodes face each other with a separator inserted between them, wherein the gel electrolyte forming composition can be coated with a volume larger than the total pore volume of the separator, the positive electrode active material layer, and the negative electrode active material layer.

[0024] Beneficial effects

[0025] According to one embodiment, the bipolar secondary battery uses a gel electrolyte formed on adjacent bipolar electrodes and separators, instead of a liquid electrolyte, thereby effectively suppressing electrolyte leakage and enabling the application of a simplified sealing structure.

[0026] In addition, the bipolar secondary battery includes a gel electrolyte in a state of being impregnated in the electrode active material layer and / or separator, and also includes a specific excess volume of gel electrolyte between the electrode active material layer and the separator.

[0027] In this way, the excess gel electrolyte formed between the electrode active material layer and the separator forms a continuous state with the gel electrolyte impregnated in these electrode active material layers and / or separators, thereby further improving the interfacial characteristics between each electrode and the gel electrolyte, enhancing the ion conductivity of the bipolar secondary battery, and reducing the resistance.

[0028] Furthermore, the excess gel electrolyte can be used as a reservoir for excess electrolyte. Therefore, even if the electrolyte contained in the gel electrolyte is consumed or volatilized due to the use of the bipolar secondary battery, the excellent electrochemical characteristics of the bipolar secondary battery can be maintained for a long period of time, and the lifetime characteristics can be further improved. Attached Figure Description

[0029] Figure 1 This is a schematic cross-sectional view of a bipolar secondary battery according to one embodiment of the present disclosure.

[0030] Figure 2 A graph showing the resistance evaluation results of the bipolar secondary batteries of Examples 1 and 2 and Comparative Example 1.

[0031] Figure 3A graph showing the results of evaluating the capacity retention of each cycle in the charge and discharge tests of the bipolar secondary batteries according to Examples 1 and 2 and Comparative Example 1. Detailed Implementation

[0032] In the following description and claims, the terms or words used should not be construed as limited to their ordinary or dictionary meanings, and this disclosure should be interpreted in a meaning and concept consistent with the technical concept of this disclosure, based on the principle that the inventor can appropriately define the concepts of the terms in order to best describe his own invention.

[0033] Unless otherwise defined, all terms used herein (including technical and scientific terms) are to be understood in the sense that would be commonly understood by one of ordinary skill in the art to which this disclosure pertains. Furthermore, unless specifically and explicitly defined, terms as defined in commonly used dictionaries should not be interpreted ideally or excessively.

[0034] The technical terminology provided herein is for the purpose of describing particular embodiments only and is not intended to limit this disclosure. Unless the context clearly indicates otherwise, the singular forms “a,” “an,” and “the” are intended to include the plural forms as well. The terms “comprising” and / or “including” as used herein do not exclude the presence or addition of one or more elements other than those mentioned.

[0035] Throughout this description, unless otherwise specified, when a part “includes” a component, it does not mean that the part excludes other components, but rather that the part may include other components.

[0036] Several embodiments of this disclosure will now be described in detail with reference to the accompanying drawings, enabling those skilled in the art to readily implement them. Identical or similar components throughout this specification and the drawings will be designated using the same reference numerals.

[0037] Reference Figure 1 According to one embodiment of the present disclosure, a bipolar secondary battery may have a structure in which a negative electrode active material layer 20 and a positive electrode active material layer 30 are respectively formed on two surfaces of a metal current collector 10. The bipolar electrodes are stacked in a plurality of layers, and the positive electrode active material layer 30 and the negative electrode active material layer 20 of the adjacent bipolar electrodes face each other with a porous separator 70 inserted between them.

[0038] In one embodiment of the bipolar secondary battery, the positive electrode active material layer 30 and the negative electrode active material layer 20, which are facing each other with a spacer 70 inserted between them, can be defined as a single cell 100. The bipolar secondary battery can have a structure in which such cells are stacked and connected in series.

[0039] Furthermore, in a bipolar secondary battery according to one embodiment, the cured gel electrolyte is contained in an impregnated state inside one or more (or all of them) of the porous separator 70, the positive electrode active material layer 30, or the negative electrode active material layer 20.

[0040] In a more specific embodiment, based on the total thickness of the porous separator 70, the positive electrode active material layer 30, and / or the negative electrode active material layer 20, the gel electrolyte may be contained in these materials in an impregnated and cured state to a thickness corresponding to 60% or more, 70% or more, 80% or more, or 90% to 100% from their surfaces.

[0041] Thus, the gel electrolyte can fill some or all of the pores present in the separator 70, the positive electrode active material layer 30 and / or the negative electrode active material layer 20, and more specifically, the gel electrolyte can fill 60% or more, 70% or more, 80% or more, or 90% to 100% of the pores relative to the total volume of the pores.

[0042] Furthermore, in one embodiment of the bipolar secondary battery, in addition to the first gel electrolyte (not shown) impregnated within the separator 70, the positive electrode active material layer 30, and / or the negative electrode active material layer 20, a second gel electrolyte 80 with excess volume or thickness is also formed between the separator 70 and the positive electrode active material layer 30 and / or between the separator 70 and the negative electrode active material layer 20 facing each other. This excess volume of the second gel electrolyte 80 can be solidified together with the first gel electrolyte impregnated within the separator 70, the positive electrode active material layer 30, and / or the negative electrode active material layer 20, thereby forming a continuous state.

[0043] By continuously forming such a first gel electrolyte and a second gel electrolyte, the interfacial properties between the first gel electrolyte and the second gel electrolyte and the positive electrode active material layer 30 and / or the negative electrode active material layer 20 can be further improved, and the conductivity of the bipolar secondary battery according to one embodiment can be further improved, and the resistance can be reduced.

[0044] To form such an excess of the second gel electrolyte 80, the volumes of the first and second gel electrolytes can be greater than the total pore volume of the separator, the positive electrode active material layer, and the negative electrode active material layer in their unimpregnated state. In a more specific embodiment, based on the total pore volume of the separator, the positive electrode active material layer, and the negative electrode active material layer in their unimpregnated state, the total volume of the first and second gel electrolytes can be 103% to 200%, or 105% to 160%, or 107% to 150%, or 108% to 130%.

[0045] At this point, the ratio of the total volume of the first gel electrolyte and the second gel electrolyte can be measured and calculated using the following method. First, the total pore volume of the separator, the positive electrode active material layer, and the negative electrode active material layer can be measured using the BET (Brunauer-Emmett-Teller) method. This can be achieved by treating the separator, the positive electrode active material layer, and the negative electrode active material layer with an organic solvent capable of dissolving the gel electrolyte, such as dimethyl carbonate, to dissolve and remove the gel electrolyte or other organic materials contained within the pores of these layers, after which the total pore volume can be measured.

[0046] Furthermore, using an analytical apparatus equipped with an electron microscope, the ratio of the first gel electrolyte impregnated and embedded within the separator, the positive electrode active material layer, and the negative electrode active material layer can be calculated, and the volume of the first gel electrolyte can be measured and calculated. Additionally, using this analytical apparatus, the thickness of the second gel electrolyte further formed between the positive electrode active material layer and / or the negative electrode active material layer and the separator can be measured, and the volume of the second gel electrolyte can be measured and calculated.

[0047] The ratio of the total volume of the first gel electrolyte and the second gel electrolyte can be calculated from the total pore volume of the separator, the positive electrode active material layer and the negative electrode active material layer, and the total volume of the first gel electrolyte and the second gel electrolyte, which are measured and calculated in this way.

[0048] In a more specific embodiment, based on the sum of the thicknesses of the positive electrode active material layer 30 and / or the negative electrode active material layer 20, the thickness of the second gel electrolyte 80 further formed between the positive electrode active material layer 30 and / or the negative electrode active material layer 20 and the separator 70 is, for example, 0.1 μm to 20 μm, or 0.5 μm to 18 μm, or 1 μm to 15 μm.

[0049] The second gel electrolyte 80, further formed to the aforementioned volume or thickness, can serve as a reservoir for excess electrolyte. Therefore, even if the electrolyte contained in the first gel electrolyte is consumed or evaporated due to continuous use of the bipolar secondary battery, the excellent electrochemical characteristics of the bipolar secondary battery can be maintained for a long period, and its lifetime characteristics can be improved. However, if the volume or thickness of the second gel electrolyte 80 becomes too large, the manufacture of the bipolar secondary battery itself may become difficult, or its energy density may decrease.

[0050] In a more specific embodiment, the second gel electrolyte 80 may be further formed between the separator 70 and the positive electrode active material layer 30, and between the separator 70 and the negative electrode active material layer 20, respectively. In this case, the second gel electrolyte 80 further formed between the separator 70 and the positive electrode active material layer 30 and / or between the separator 70 and the negative electrode active material layer 20 may have a uniform volume and thickness.

[0051] For example, based on the total pore volume of the separator 70, the positive electrode active material layer 30, and the negative electrode active material layer 20 in the unimpregnated state with gel electrolyte, each of these second gel electrolytes 80 can be formed with an excess volume corresponding to 2% to 60%, or 2.5% to 50%, or 3% to 30%, or 3.5% to 20%. Furthermore, the thickness of each of these second gel electrolytes 80 can be 0.05 μm to 20 μm, or 0.1 μm to 15 μm, or 0.5 μm to 8 μm.

[0052] Because the excess second gel electrolyte 80 is formed in such a uniform volume or thickness between the separator 70 and the positive electrode active material layer 30 and between the separator 70 and the negative electrode active material layer 20, the battery of one embodiment can maintain improved conductivity and electrochemical characteristics for a long period of time.

[0053] On the other hand, in a bipolar secondary battery according to one embodiment, the bipolar electrode may include a metal current collector 10. For reference, due to the structural characteristics of the bipolar secondary battery in which the cell units 100 are connected in series, the metal current collector 10 needs to exhibit electrochemical stability over a wide voltage range. In a bipolar secondary battery according to one embodiment, taking into account these requirements and the excellent adhesion of the positive electrode active material layer 20 and the negative electrode active material layer 30 to the metal current collector 10, the metal current collector 10 may include a stainless steel metal current collector, or may include a stacked current collector made of aluminum and copper, such as a stacked current collector including aluminum layers and copper layers, wherein the aluminum layer faces the positive electrode active material layer 30 and the copper layer faces the negative electrode active material layer 20.

[0054] A positive electrode active material layer 30 is formed on one surface of the metal current collector 10. This positive electrode active material layer 30 may comprise a polymer binder, a conductive material, and a positive electrode active material, and can be formed by coating a slurry composition in which the polymer binder, conductive material, and positive electrode active material are dispersed in an organic solvent onto one surface of the metal current collector 10 and then drying it. In another embodiment of this disclosure, the positive electrode active material layer 30 can be formed by dry mixing the polymer binder, conductive material, and positive electrode active material, forming the polymer binder into a fibrous powder under shear force, and then forming it into a film through a calendering process. However, since the wet or dry manufacturing methods of such a positive electrode active material layer 30 and the form of the resulting positive electrode active material layer 30 are obvious to those skilled in the art, further description thereof will be omitted.

[0055] Meanwhile, lithium transition metal oxides, lithium metal phosphates, metal oxides, etc., can be used as the positive electrode active material contained in the positive electrode active material layer 30 without any particular restrictions. Specific examples of such positive electrode active materials include: layered compounds, such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or compounds substituted with one or more transition metals; lithium manganese oxide, such as Li... 1+x Mn 2-x O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, LiFe3O4, V2O5 and Cu2V2O7; and LiNi 1-x M x Ni-site type lithium nickel oxides represented by O2 (where M = Co, Mn, Al, Cu, Fe, Mg, Ca, Zr, Ti, B, P, W, Si, Na, K, Mo, V, Nb, Ru, or Ga, and x = 0.01 to 0.3); LiMn 2-x M x Lithium manganese composite oxides represented by O2 (M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); LiMn2O4 in which some Li atoms are replaced by alkaline earth metal ions; lithium metal phosphate LiMPO4 (where M is Fe, Co, Ni or Mn); disulfide compounds; Fe2(MoO4)3; and so on, but not limited to these.

[0056] Considering the operating voltage, unit cost, physical and electrochemical properties of bipolar secondary batteries, lithium transition metal phosphate LiMPO4 (where M = Fe, Co, Ni or Mn) can be preferably used, more specifically lithium iron phosphate as the positive electrode active material.

[0057] Based on the total weight of the positive electrode active material layer 30, the positive electrode active material may be included in an amount of, for example, 80% to 99% by weight, or 85% to 98% by weight.

[0058] Furthermore, any polymer binder previously known for use in electrode active material layers of lithium secondary batteries can be used as the polymer binder for the positive electrode active material layer 30 without any particular limitations. Specific examples of such polymer binders may include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, or various copolymers thereof.

[0059] Typically, based on the total weight of the positive electrode active material layer 30, the polymer binder may be included in an amount of 0.5% to 15% by weight, or 0.7% to 10% by weight.

[0060] Furthermore, there are no particular limitations on the conductive material included in the positive electrode active material layer 30, as long as it is conductive and does not cause chemical changes in the battery. For example, graphite, such as natural or artificial graphite; graphene; activated carbon; activated carbon fibers; carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal cracking black; conductive fibers, such as carbon fibers or metal fibers; metal powders, such as fluorinated carbon powder, aluminum powder, and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; conductive materials, such as polyphenylene derivatives; etc. However, specifically, the conductive material may include at least one selected from activated carbon, graphite, carbon black, graphene, and single-walled or multi-walled carbon nanotubes to ensure uniform mixing and improve conductivity, and more specifically, it may include carbon black or activated carbon.

[0061] Based on the total weight of the positive electrode active material layer 30, the conductive material may be included in an amount of 0.1% to 15% by weight, or 0.5% to 10% by weight.

[0062] In some cases, the positive electrode active material layer 30 may also include a filler as a component for suppressing electrode expansion. There are no particular limitations on the filler, as long as it is a fibrous material and does not induce chemical changes in the battery. For example, it may be made of: olefin-based polymers, such as polyethylene or polypropylene; or fibrous materials, such as glass fiber or carbon fiber.

[0063] Furthermore, if it is necessary to further improve the adhesion between the metal current collector 10 and the positive electrode active material layer 30, an underlayer can be further formed between them. This underlayer can contain, for example, conductive materials and adhesives, and can further improve the adhesion properties of the positive electrode active material layer 30 to the metal current collector 10.

[0064] Here, a component equivalent to the conductive material contained in the positive electrode active material layer 30 can be used as the conductive material. Furthermore, examples of binders that can be used include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butene rubber, fluororubber, etc.

[0065] In this case, based on the total weight of the underlayer, the content of conductive material can be 5% to 50% by weight, or 5% to 30% by weight, or 10% to 30% by weight. If the content of conductive material is too low, the resistance of the bipolar electrode may increase, while if the content of conductive material is too high, the adhesion strength between the positive electrode active material layer 30 and the metal current collector 10 may decrease. Furthermore, an adhesive may be included as an underlayer to eliminate excess conductive material. The underlayer can be formed to a thickness of, for example, 0.1 μm to 10 μm.

[0066] Meanwhile, in the bipolar secondary battery, a negative electrode active material layer 20 is formed on another surface of the metal current collector 10. The negative electrode active material layer 20 may comprise a polymer binder, a conductive material, and a negative electrode active material, and may be formed by coating a slurry composition in which the polymer binder, conductive material, and negative electrode active material are dispersed in an organic solvent onto one surface of the metal current collector 10 and then drying it.

[0067] In the negative electrode active material layer 20, the negative electrode active material may include graphite-based active materials, such as non-graphitized carbon and graphite-based carbon; metal composite oxides, such as Li x Fe2O3 (0≤x≤1), Li x WO2 (0≤x≤1), Sn x Me 1-x Me' y Oz (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, Group 2 and Group 3 elements in the periodic table, halogen; 0<x≤1; 1≤y≤3; 1≤z≤8); lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; silicon-based oxide, such as SiO, SiO / C, SiO x (1<x<2) and SiO₂; metal oxides, such as SnO, SnO₂, PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, Sb₂O₅, GeO, GeO₂, Bi₂O₃, Bi₂O₄ and Bi₂O₅; conductive polymers, such as polyacetylene; or Li-Co-Ni based materials. In consideration of factors such as favorable formation of the negative active material layer 20 on the metal current collector 10, driving voltage and unit price of the bipolar secondary battery, a graphite-based active material is preferably used as the negative active material.

[0068] The negative active material may be included in an amount of, for example, 80 wt% to 99 wt% or 85 wt% to 98 wt%, based on the total weight of the negative active material layer 20.

[0069] On the other hand, the types and amounts of the polymer binder, the conductive material, and the additive that may be included in the negative active material layer 20 are substantially the same as those described for the positive active material layer 30, and thus, further description thereof will be omitted.

[0070] A plurality of the above-described bipolar electrodes each including the negative active material layer 20 and the positive active material layer 30 respectively formed on both surfaces of the metal current collector 10 are stacked. As already mentioned above, to ensure that the unit cells 100 each defined by the negative active material layer 20 and the positive active material layer 30 facing each other, the separator 70 therebetween, and the first gel electrolyte and the second gel electrolyte are connected in series, in the mutually adjacent bipolar electrodes, the negative active material layer 20 of one bipolar electrode and the positive active material layer 30 of the other bipolar electrode face each other with the porous separator 70 interposed therebetween. Further, as described above, the first gel electrolyte impregnated into the interior of each of these active material layers and the separator, and the second gel electrolyte 80 between these active material layers and the separator may be formed.

[0071] On the other hand, the first gel electrolyte and the second gel electrolyte can be composed of the same or similar compositions. More specifically, the first gel electrolyte and the second gel electrolyte can comprise a matrix containing a crosslinked polymer and an electrolyte impregnated in the matrix. More specifically, the matrix can comprise a crosslinked polymer cured from a polyfunctional (meth)acrylate-based compound having difunctional or more functional (meth)acrylate groups or difunctional to hexafunctional (meth)acrylate groups. Such a matrix enables the stable formation of the first gel electrolyte and the second gel electrolyte, and enables the electrolyte impregnated in the matrix to be uniformly and stably retained.

[0072] Examples of polyfunctional (meth)acrylate compounds that can be used to form such a matrix are not particularly limited, and may include, for example, one or more selected from trimethylolpropane ethoxylate triacrylate (ETPTA), trimethylolpropane ethoxylate triacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, and tri(2-hydroxyethyl)isocyanurate triacrylate.

[0073] In both the first gel electrolyte and the second gel electrolyte, the matrix contains an electrolyte in a uniformly impregnated state, and the electrolyte contains a lithium salt.

[0074] Lithium salts are used as a medium for transferring ions within secondary batteries. For example, lithium salts can contain Li as a cation. + And as an anion, it is selected from at least one of the following: F - Cl - ,Br - I - NO3 - N(CN)2 - BF4 - ClO4 - B 10 Cl 10 - AlCl4 - AlO2 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - (CF3CF2SO2)2N - (CF3SO2)2N - (FSO2)2N - BF2C2O4 - BC4O8 -PF4C2O4 - PF2C4O8 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - (CF3SO2)2CH - CF3(CF2)7SO3 - and SCN - .

[0075] Specifically, lithium salts may include those selected from LiCl, LiBr, LiI, LiBF4, LiClO4, and LiB. 10 Cl 10 One or a mixture of two or more of the following: LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(perfluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2) and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2), and LiPF6, LiFSI, or mixtures thereof may be used suitably for the purpose of excellent stability.

[0076] The concentration of the lithium salt can be appropriately varied within a generally applicable range, and considering the output characteristics and stability of a secondary battery in one embodiment, the lithium salt can be included in the electrolyte at a concentration of 0.5 M to 3 M, particularly 1 M to 2.5 M, and even more particularly 1 M to 2 M. When the concentration of the lithium salt meets the above range, the effect on improving the cycle characteristics of the lithium secondary battery is sufficient, and the viscosity is suitable, thereby improving the electrolyte impregnation characteristics.

[0077] In addition to lithium salt, the electrolyte also contains non-aqueous organic solvents, including non-volatile carbonate-based solvents with boiling points of 150°C or higher, 170°C to 270°C, or 200°C to 250°C, and non-volatile lactone-based solvents with boiling points of 150°C or higher, 170°C to 270°C, or 200°C to 250°C.

[0078] By using this combination of non-volatile solvents, the volatilization of electrolyte from the first and second gel electrolytes during the manufacture and use of a battery in one embodiment can be effectively suppressed. Furthermore, by combining carbonate-based and lactone-based solvents, the ionic conductivity of the first and second gel electrolytes, as well as the bipolar secondary battery comprising them, can be improved.

[0079] As a non-volatile carbonate-based solvent, for example, one or more selected from ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate can be used; and as a non-volatile lactone-based solvent, for example, one or more selected from γ-butyrolactone, acetyl lactone, β-propiolactone, and δ-valerolactone can be used.

[0080] On the other hand, considering the solubility of lithium salts and the non-volatility of electrolytes, non-aqueous organic solvents may also include non-volatile sulfone-based solvents with boiling points of 150°C or higher, 170°C to 270°C, or 200°C to 250°C. As such non-volatile sulfone-based solvents, one or more selected from dimethyl sulfone, ethylmethyl sulfone, and diethyl sulfone can be used. Such non-volatile sulfone-based solvents can be used in amounts replacing one or more of non-volatile carbonate-based solvents or non-volatile lactone-based solvents, for example, 5% or more by weight, 10% or more by weight, or 15% to 30% by weight.

[0081] Furthermore, considering the ionic conductivity of the secondary battery in one embodiment, as well as the low volatility and appropriate viscosity of the electrolyte, the non-aqueous organic solvent may comprise non-volatile carbonate-based solvents and non-volatile lactone-based solvents in a weight ratio of 50:50 to 10:90, or 60:40 to 15:90, or 70:30 to 20:80.

[0082] Simultaneously, the total amount of non-volatile carbonate-based solvents and non-volatile lactone-based solvents is 100 parts by weight, and the non-aqueous organic solvent may also contain 1 to 10 parts by weight, or 2 to 8 parts by weight, of a difluoroalkyl ether-based compound. In a more specific example, the difluoroalkyl ether-based compound may include one or more of the following: 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), bis(2,2,2-trifluoroethyl) ether (BTFE), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (TFTFE), 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether (OTE), 1,2-bis(1,1,2,2-tetrafluoroethoxy)ethane (TFEE), and bis(2,2,2-trifluoroethoxy)ethane.

[0083] Compounds based on difluoroalkyl ethers can be incorporated into the electrolyte to reduce its surface tension and contact angle, thereby improving the wettability of the electrolyte. As a result, when such difluoroalkyl ether-based compounds are further used, the electrolyte and the composition comprising it that forms the gel electrolyte can be more uniformly impregnated into the positive electrode active material layer 30 or the negative electrode active material layer 20 during the formation process of the first and second gel electrolytes, and this makes it possible to form the first and second gel electrolytes more uniformly and easily. Therefore, a secondary battery comprising a first and second gel electrolyte in one embodiment can exhibit excellent physical and electrochemical properties.

[0084] In one specific embodiment, the electrolyte, which comprises a difluoroalkyl ether-based compound, can exhibit a surface tension of 30 mN / m to 60 mN / m, or 35 mN / m to 55 mN / m, or 35 mN / m to 45 mN / m and a contact angle of 30° to 60°, or 35° to 55°, or 35° to 52°, thereby exhibiting excellent wettability to the positive electrode active material layer 30 or the negative electrode active material layer 20.

[0085] In addition, considering ion conductivity, safety, or stability, the electrolyte may also contain one or more additives selected from vinylene carbonate, fluoroethylene carbonate, and ethylene sulfate, and such additives may be included in an amount of 1 to 5 parts by weight based on a total of 100 parts by weight of non-volatile carbonate-based solvents and non-volatile lactone-based solvents.

[0086] Furthermore, in a bipolar secondary battery according to one embodiment, a porous separator 70 supporting a second gel electrolyte 80 is also included between the positive electrode active material layer 30 and the negative electrode active material layer 20 of the adjacent bipolar electrodes.

[0087] The porous separator 70 can be a porous polymer membrane containing polyolefin-based polymers (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a stacked structure of two or more layers thereof.

[0088] Furthermore, the separator can be an uncoated separator comprising only a porous polymer membrane, but it can also be a coated separator in which a coating comprising a binder and inorganic particles is formed on one or both surfaces of the substrate comprising the porous polymer membrane. An example of such a coated separator is an SRS (Safety Reinforced Separator), the structure of which will be apparent to those skilled in the art.

[0089] Meanwhile, in a bipolar secondary battery according to one embodiment, the electrode terminals electrically connected to the current collector can be directly or indirectly connected to the outermost current collector 10 on both sides in the stacking direction of the cell 100, either directly or indirectly via a separate current collector plate. Furthermore, the bipolar secondary battery can be housed in a separate case, and the electrode terminals can be connected to the outside of the case.

[0090] Meanwhile, according to another embodiment of this disclosure, a method for manufacturing the above-mentioned bipolar secondary battery is provided. The manufacturing method may include: a first step of forming a negative electrode active material layer and a positive electrode active material layer on two surfaces of a metal current collector to manufacture a bipolar electrode; a second step of coating the negative electrode active material layer or the positive electrode active material layer with a composition comprising a curable multifunctional compound and an electrolyte to form a gel electrolyte and then curing it; a third step of coating the composition forming the gel electrolyte onto at least one surface of a separator and then curing it; and a fourth step of stacking the bipolar electrodes in a plurality of stacks such that the positive electrode active material layers and negative electrode active material layers of adjacent bipolar electrodes face each other with a separator inserted between them.

[0091] In manufacturing methods according to other embodiments, for example, in a second or third step, the composition forming the gel electrolyte may be used in an excessive amount or volume. For example, the composition forming the gel electrolyte may be coated and cured in a volume larger than the total pore volume of the separator, the positive electrode active material layer, and the negative electrode active material layer. Thus, after the second or third step, an additional second gel electrolyte having an excessive volume or thickness may be formed on at least one surface of the separator or on the negative electrode active material layer or the positive electrode active material layer.

[0092] According to a more specific embodiment, in the third step of forming a gel electrolyte on one or both surfaces of the separator, an additional second gel electrolyte having the volume or thickness already described above can be formed on one or both surfaces of the separator by using an excessive amount or volume of the gel electrolyte-forming composition. In this case, in the second step, the gel electrolyte-forming composition can be used to the extent that the first gel electrolyte can be completely impregnated within the negative electrode active material layer and / or the positive electrode active material layer.

[0093] On the other hand, if a first gel electrolyte and a second gel electrolyte are formed in a second or third step, and then bipolar electrodes are stacked with a separator inserted between them, a bipolar secondary battery of such an embodiment can be manufactured, wherein a second gel electrolyte with an excess thickness or volume is further formed between the separator and the positive or negative active material layer facing each other.

[0094] In this manufacturing method, the amount of the composition used in the second and third steps to form the gel electrolyte can be appropriately determined by those skilled in the art by taking into account the total pore volume of the separator, the positive electrode active material layer and the negative electrode active material layer, as well as the volume / thickness of the second gel electrolyte to be further formed between them.

[0095] Simultaneously, in this manufacturing method, firstly, a negative electrode active material layer and a positive electrode active material layer are formed on both surfaces of the metal current collector to manufacture a bipolar electrode. At this time, the negative electrode active material layer and the positive electrode active material layer can be formed by a wet process, which involves coating a slurry composition comprising a polymer binder, a conductive material, a negative electrode active material or a positive electrode active material, and an organic solvent, followed by drying and rolling. Since the process for forming such positive electrode active material layers and negative electrode active material layers can follow a general wet electrode process, further description of it will be omitted.

[0096] Furthermore, in other embodiments, the positive electrode active material layer can be formed as a self-supporting film using a dry process. This dry process involves dry mixing a fiberizable polymer binder (e.g., PTFE), a conductive material, and the positive electrode active material, forming a powder under shear force, followed by a calendering process. Such a dry manufacturing process for the positive electrode active material layer can follow typical dry electrode film formation processes disclosed, for example, in U.S. Patent Nos. 8,815,443 or 10,153,096.

[0097] In one example, the positive electrode active material layer can be prepared by: dry mixing positive electrode active material particles, a fiberizable polymer binder, and conductive material particles; applying shear force to the dry mixture to fiberize the polymer binder to form a dry electrode powder; and calendering the resulting product into a film.

[0098] Simultaneously, after forming the bipolar electrodes, a composition comprising a polyfunctional (meth)acrylate-based compound and an electrolyte to form a gel electrolyte can be coated onto the negative electrode active material layer or the positive electrode active material layer. In this case, the composition of the electrolyte is the same as described above for a bipolar secondary battery according to one embodiment.

[0099] Furthermore, based on 100 parts by weight of the electrolyte, the polyfunctional (meth)acrylate-based compound can be included in the composition forming the gel electrolyte in amounts of 3 to 20 parts by weight, 4 to 15 parts by weight, or 5 to 13 parts by weight. This allows for the advantageous formation of a matrix and gel electrolyte uniformly impregnated with the electrolyte, and ensures excellent conductivity of the gel electrolyte layer.

[0100] After coating the composition forming the gel electrolyte, the surface of the negative or positive electrode active material layer on which the composition forming the gel electrolyte has been coated can be uniformly pressed to impregnate the composition into the negative or positive electrode active material layer. Thus, the composition forming the gel electrolyte can uniformly penetrate into the negative or positive electrode active material layer, thereby uniformly forming a first gel electrolyte and a second gel electrolyte that at least partially overlap with the negative or positive electrode active material layer and optionally have additional volume or thickness on the active material layer. In a more specific embodiment, the step of impregnating the composition forming the gel electrolyte can be performed by uniformly rolling the surface of the negative or positive electrode active material layer on which the composition forming the gel electrolyte has been coated.

[0101] Simultaneously, after the impregnation step, heat or ultraviolet light can be irradiated onto the coated composition forming the gel electrolyte to thermally or photocur the polyfunctional (meth)acrylate-based compound. This advantageously forms a matrix comprising a crosslinked polymer containing a polyfunctional (meth)acrylate-based compound, and a first gel electrolyte and a second gel electrolyte impregnated into the matrix.

[0102] In this case, there are no particular restrictions on the conditions for the curing step, and curing can be carried out under appropriate curing conditions based on the type and content of the polyfunctional (meth)acrylate compound. However, in one specific embodiment, the curing step can be carried out by irradiating with ultraviolet light for 3 seconds to 5 minutes, or 5 seconds to 1 minute, in the presence of an impermeable membrane that prevents the passage of oxygen or other substances that inhibit free radical photocuring reactions.

[0103] Simultaneously, the composition for forming the gel electrolyte can be coated not only on the negative electrode active material layer or the positive electrode active material layer, but also on at least one surface of the separator and cured to form a first gel electrolyte and a second gel electrolyte on the separator. In this case, an excessive amount of the composition for forming the gel electrolyte can be used, resulting in an excessive volume or thickness of the second gel electrolyte on the separator, and these points are the same as described above.

[0104] Since the composition of the gel electrolyte formed by coating the separator is consistent with the composition used in the previously described second step, further description thereof will be omitted. Furthermore, the conditions of the rolling process, such as those for coating, curing, and impregnating the composition for forming the gel electrolyte on the separator, are the same as those described in the second step, and therefore, further description thereof will be omitted.

[0105] After forming a bipolar electrode comprising a first gel electrolyte and a second gel electrolyte through the aforementioned curing process, the bipolar electrodes can be stacked in plurality of stacks such that the positive and negative active material layers of adjacent bipolar electrodes face each other with the first and second gel electrolytes and spacers inserted between them. This allows the manufacture of a bipolar secondary battery according to one embodiment. In this case, the first gel electrolyte forming surfaces and / or the second gel electrolyte forming surfaces of the active material layers and spacers can contact each other to further improve the battery's ionic conductivity.

[0106] The above implementation scheme will be described in more detail below with reference to specific embodiments.

[0107] Comparative Example 1: Manufacturing of Bipolar Secondary Cells

[0108] 96 g of LiFePO4 as the positive electrode active material, 0.5 g of carbon black as the conductive material, and 3.5 g of polytetrafluoroethylene (PTFE) as the binder were placed in a mixer and dry-mixed at 10,000 rpm for 1 minute to prepare a mixture. The temperature of the kneader was stabilized at 150°C, and the mixture was placed in the kneader and then run at 50 rpm for 5 minutes under a pressure of 1.1 atm to obtain a mixture block.

[0109] The resulting mixture was placed in a mixer and pulverized at 10,000 rpm for 40 seconds, then classified through a sieve with a 1 mm aperture to obtain electrode powder. The prepared electrode powder was then subjected to several passes through a laboratory calender (roller diameter: 88 mm, roll temperature: 100 °C) to produce an electrode powder with a concentration of 600 mg / 25 cm⁻¹. 2 The positive electrode active material layer has an electrode layer loading and a thickness of 100 μm and is in the form of a self-supporting film. The positive electrode active material layer is attached to one surface of a stainless steel foil (8 μm) and rolled.

[0110] On the other hand, 96 g of graphite as the negative electrode active material, 1.0 g of Super C-65 as the conductive material, and 3.0 g of SBR binder and thickener were mixed in an organic solvent to prepare a slurry. The slurry was coated onto another surface of a stainless steel foil (8 μm), dried, and rolled to form a negative electrode active material layer.

[0111] On the other hand, based on a solvent in which 100 parts by weight of ethylene carbonate (boiling point: about 238°C) and γ-butyrolactone (boiling point: about 204°C) are mixed in a weight ratio of 2:8, 3 parts by weight of ethylene carbonate and 0.5 parts by weight of ethylene sulfate are mixed. 1 M LiPF6 is added to this non-aqueous organic solvent to prepare an electrolyte, and 5 parts by weight of trimethylolpropane ethoxylate triacrylate is mixed with 100 parts by weight of the electrolyte to prepare a composition forming a gel electrolyte.

[0112] Next, 0.2 g of the gel-forming electrolyte composition was drop-added and coated onto the positive and negative electrode active material layers, and the coated surfaces were rolled to impregnate the gel-forming electrolyte composition into the negative and positive electrode active material layers, respectively. Then, UV light was applied at 600 W / cm². 2 The intensity of the irradiation is applied to the coated surface for 5 seconds to form a gel electrolyte.

[0113] Bipolar electrodes with gel electrolytes formed on the positive and negative electrode active material layers are stacked in multiples via porous polyethylene separators with a thickness of 5 μm to manufacture a bipolar secondary battery of Comparative Example 1.

[0114] Example 1: Manufacturing of a bipolar secondary battery

[0115] 96 g of LiFePO4 as the positive electrode active material, 0.5 g of carbon black as the conductive material, and 3.5 g of polytetrafluoroethylene (PTFE) as the binder were placed in a mixer and dry-mixed at 10,000 rpm for 1 minute to prepare a mixture. The temperature of the kneader was stabilized at 150°C, and the mixture was placed in the kneader and then run at 50 rpm for 5 minutes under a pressure of 1.1 atm to obtain a mixture block.

[0116] The resulting mixture was placed in a mixer and pulverized at 10,000 rpm for 40 seconds, then classified through a sieve with a 1 mm aperture to obtain electrode powder. The prepared electrode powder was then subjected to several passes through a laboratory calender (roller diameter: 88 mm, roll temperature: 100 °C) to produce an electrode powder with a concentration of 600 mg / 25 cm⁻¹. 2 The positive electrode active material layer has an electrode layer loading and a thickness of 100 μm and is in the form of a self-supporting film. The positive electrode active material layer is attached to one surface of a stainless steel foil (8 μm) and rolled.

[0117] On the other hand, 96 g of graphite as the negative electrode active material, 1.0 g of Super C-65 as the conductive material, and 3.0 g of SBR binder and thickener were mixed in an organic solvent to prepare a slurry. The slurry was coated onto another surface of a stainless steel foil (8 μm), dried, and rolled to form a negative electrode active material layer.

[0118] On the other hand, based on a solvent in which 100 parts by weight of ethylene carbonate (boiling point: about 238°C) and γ-butyrolactone (boiling point: about 204°C) are mixed in a weight ratio of 2:8, 3 parts by weight of ethylene carbonate and 0.5 parts by weight of ethylene sulfate are mixed. 1 M LiPF6 is added to this non-aqueous organic solvent to prepare an electrolyte, and 5 parts by weight of trimethylolpropane ethoxylate triacrylate is mixed with 100 parts by weight of the electrolyte to prepare a composition forming a gel electrolyte.

[0119] Next, 0.2 g of the gel-forming electrolyte composition was drop-added and coated onto the positive and negative electrode active material layers, and the coated surfaces were rolled to impregnate the gel-forming electrolyte composition into the negative and positive electrode active material layers, respectively. Then, UV light was applied at 600 W / cm². 2 The intensity of the irradiation is applied to the coated surface for 5 seconds to form a gel electrolyte.

[0120] On the other hand, approximately 0.08 g of the composition for forming the gel electrolyte was drop-added and coated onto one surface of a 5 μm thick porous polyethylene separator, and the coated surface was rolled to impregnate the gel electrolyte composition into the separator. At this point, the composition not impregnated into the separator remained on one surface of the separator as is to form a gel electrolyte of additional thickness. Then, UV light was applied at 600 W / cm². 2 The intensity of the irradiation is applied to the coated surface for 5 seconds to form a gel electrolyte.

[0121] The bipolar electrodes are stacked in multiples via the porous polyethylene separator, such that the gel electrolyte forming surfaces of each active material layer and the separator are adjacent to each other, thereby manufacturing the bipolar secondary battery of Example 1.

[0122] Example 2: Manufacturing of a bipolar secondary battery

[0123] 96 g of LiFePO4 as the positive electrode active material, 0.5 g of carbon black as the conductive material, and 3.5 g of polytetrafluoroethylene (PTFE) as the binder were placed in a mixer and dry-mixed at 10,000 rpm for 1 minute to prepare a mixture. The temperature of the kneader was stabilized at 150°C, and the mixture was placed in the kneader and then run at 50 rpm for 5 minutes under a pressure of 1.1 atm to obtain a mixture block.

[0124] The resulting mixture was placed in a mixer and pulverized at 10,000 rpm for 40 seconds, then classified through a sieve with a 1 mm aperture to obtain electrode powder. The prepared electrode powder was then subjected to several passes through a laboratory calender (roller diameter: 88 mm, roll temperature: 100 °C) to produce an electrode powder with a concentration of 600 mg / 25 cm⁻¹. 2 The positive electrode active material layer has an electrode layer loading and a thickness of 100 μm and is in the form of a self-supporting film. The positive electrode active material layer is attached to one surface of a stainless steel foil (8 μm) and rolled.

[0125] On the other hand, 96 g of graphite as the negative electrode active material, 1.0 g of Super C-65 as the conductive material, and 3.0 g of SBR binder and thickener were mixed in an organic solvent to prepare a slurry. The slurry was coated onto another surface of a stainless steel foil (8 μm), dried, and rolled to form a negative electrode active material layer.

[0126] On the other hand, based on a solvent in which 100 parts by weight of ethylene carbonate (boiling point: about 238°C) and γ-butyrolactone (boiling point: about 204°C) are mixed in a weight ratio of 2:8, 3 parts by weight of ethylene carbonate and 0.5 parts by weight of ethylene sulfate are mixed. 1 M LiPF6 is added to this non-aqueous organic solvent to prepare an electrolyte, and 5 parts by weight of trimethylolpropane ethoxylate triacrylate is mixed with 100 parts by weight of the electrolyte to prepare a composition forming a gel electrolyte.

[0127] Next, 0.2 g of the gel-forming electrolyte composition was drop-added and coated onto the positive and negative electrode active material layers, and the coated surfaces were rolled to impregnate the gel-forming electrolyte composition into the negative and positive electrode active material layers, respectively. Then, UV light was applied at 600 W / cm². 2 The intensity of the irradiation is applied to the coated surface for 5 seconds to form a gel electrolyte.

[0128] On the other hand, approximately 0.02 g of the composition for forming the gel electrolyte was drop-added and coated onto one surface of a 5 μm thick porous polyethylene separator, and the coated surface was rolled to impregnate the gel electrolyte composition into the separator. At this point, the composition not impregnated into the separator remained on one surface of the separator as is to form a gel electrolyte of additional thickness. Then, UV light was applied at 600 W / cm². 2 The intensity of the irradiation is applied to the coated surface for 5 seconds to form a gel electrolyte.

[0129] The bipolar electrodes are stacked in multiples via the porous polyethylene separator, such that the gel electrolyte forming surfaces of each active material layer and the separator are adjacent to each other, thereby manufacturing the bipolar secondary battery of Example 2.

[0130] Test Example 1: Measurement of the total volume ratio of gel electrolytes

[0131] For the bipolar secondary batteries of Examples 1 and 2 and Comparative Example 1, the ratio of the total volume of the gel electrolyte was measured and calculated by the following method.

[0132] First, the total pore volume of the separator, positive electrode active material layer, and negative electrode active material layer was measured using the BET (Brunauer-Emmett-Teller) method. Specifically, the total pore volume was measured and calculated from a nitrogen adsorption isotherm obtained at 77 K in a liquid nitrogen atmosphere using BELSORP-MAX (MicrotracBEL Corp.).

[0133] When measuring the total pore volume, if the gel electrolyte has already formed on the separator, positive electrode active material layer, or negative electrode active material layer, the gel electrolyte or other organic materials contained within the pores of the separator, positive electrode active material layer, and negative electrode active material layer are treated with dimethyl carbonate organic solvent to dissolve and remove them, and then the total pore volume is measured. The total pore volumes of the separator, positive electrode active material layer, and negative electrode active material layer measured in this way are summarized in Table 1 below.

[0134] Simultaneously, using an analytical apparatus equipped with an electron microscope, the ratio of gel electrolytes impregnated and embedded in the separator, positive electrode active material layer, and negative electrode active material layer is calculated, and the volume of the first gel electrolyte is measured and calculated. Furthermore, using the same analytical apparatus, the thickness of the second gel electrolyte further formed between the positive electrode active material layer and / or the negative electrode active material layer and the separator is measured, and the formation area of ​​the second gel electrolyte is also measured. The volume of the second gel electrolyte is then measured and calculated.

[0135] The ratio of the total volume of the first gel electrolyte and the second gel electrolyte is calculated from the total pore volume of the separator, the positive electrode active material layer and the negative electrode active material layer, as well as the total volume of the first gel electrolyte and the second gel electrolyte, as measured and calculated above, and the results are summarized in Table 2 below.

[0136] [Table 1]

[0137]

[0138] [Table 2]

[0139]

[0140] Referring to Tables 1 and 2, it was determined that in the bipolar secondary batteries of Examples 1 and 2, the gel electrolyte was formed with an excess volume of 103% to 200% or 105% to 120% based on the total pore volume of the separator, the positive electrode active material layer and the negative electrode active material layer, thereby forming a second gel electrolyte with an additional thickness between each active material layer and the separator.

[0141] Test Example 2: Evaluation of Electrochemical Properties

[0142] The bipolar secondary batteries of the examples and comparative examples were charged under conditions of applying 0.1 C and approximately 6.5 mA. While applying a current of 2.5 C and 16.25 mA individually at 50% state of charge (SOC), the initial single-cell resistance was evaluated using a resistance measurement device, and the evaluation results are shown below. Figure 2 middle.

[0143] On the other hand, charge and discharge tests were performed using the bipolar secondary batteries of the examples and comparative examples under conditions of applying 0.33 C and approximately 21.5 mA. The capacity retention of each cycle was evaluated during these charge-discharge tests, and the results are shown below. Figure 3 During this capacity retention assessment, two individual cells manufactured under identical conditions were subjected to charge and discharge tests to re-establish the consistency of the test results.

[0144] Reference Figure 2 It was determined that, compared to Comparative Example 1, the bipolar secondary cells of Examples 1 and 2 exhibited lower single-cell resistance. Furthermore, referring to... Figure 3 The bipolar secondary batteries of Examples 1 and 2 were found to exhibit a capacity retention of 90% or higher up until about 180 cycles, while the battery of Comparative Example 1 showed a rapid decline in capacity retention at about 70 cycles.

Claims

1. A bipolar secondary battery, characterized in that: The bipolar electrodes, consisting of a negative electrode active material layer and a positive electrode active material layer, are formed on two surfaces of the metal current collector and stacked in multiple layers. The positive and negative active material layers of adjacent bipolar electrodes face each other with a spacer inserted between them. One or more of the separator, the positive electrode active material layer, and the negative electrode active material layer are impregnated with a gel electrolyte, and Based on the total pore volume of the separator, the positive electrode active material layer, and the negative electrode active material layer in the state without impregnation with the gel electrolyte, the gel electrolyte is formed with a volume corresponding to 103% to 200%.

2. The bipolar secondary battery according to claim 1, wherein the metal current collector includes a current collector comprising stainless steel, or a stacked current collector made of aluminum and copper.

3. The bipolar secondary battery according to claim 1, wherein the negative electrode active material layer comprises a graphite-based negative electrode active material, and the positive electrode active material layer comprises a lithium transition metal phosphate-based positive electrode active material.

4. The bipolar secondary battery of claim 1, wherein the gel electrolyte comprises a matrix and an electrolyte impregnated in the matrix, the matrix containing a crosslinked polymer based on a polyfunctional (meth)acrylate compound.

5. The bipolar secondary battery according to claim 4, wherein the electrolyte comprises: Lithium salts; and A non-aqueous organic solvent comprising a non-volatile carbonate-based solvent with a boiling point of 150°C or higher and a non-volatile lactone-based solvent with a boiling point of 150°C or higher.

6. The bipolar secondary battery according to claim 4, wherein the compound based on polyfunctional (meth)acrylate comprises one or more selected from trimethylolpropane ethoxylate triacrylate (ETPTA), trimethylolpropane ethoxylate triacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, and tri(2-hydroxyethyl)isocyanurate triacrylate.

7. The bipolar secondary battery according to claim 5, wherein the non-volatile carbonate-based solvent comprises one or more selected from ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate.

8. The bipolar secondary battery according to claim 5, wherein the non-volatile lactone-based solvent comprises one or more selected from γ-butyrolactone, acetyllactone, β-propiolactone, and δ-valerolactone.

9. The bipolar secondary battery of claim 5, wherein the non-volatile carbonate-based solvent and the non-volatile lactone-based solvent are contained in a weight ratio of 50:50 to 10:

90.

10. The bipolar secondary battery according to claim 5, wherein the non-aqueous organic solvent further comprises a non-volatile sulfone-based solvent with a boiling point of 150°C or higher.

11. The bipolar secondary battery of claim 5, wherein, based on a total of 100 parts by weight of the non-volatile carbonate-based solvent and the non-volatile lactone-based solvent, the non-aqueous organic solvent further comprises 1 to 10 parts by weight of a difluoroalkyl ether-based compound.

12. The bipolar secondary battery according to claim 1, wherein the gel electrolyte comprises: A first gel electrolyte impregnated in one or more of the separator, the positive electrode active material layer, and the negative electrode active material layer, and A second gel electrolyte is further formed between the positive electrode active material layer or the negative electrode active material layer and the separator, facing each other.

13. The bipolar secondary battery according to claim 12, wherein the first gel electrolyte and the second gel electrolyte are formed continuously.

14. The bipolar secondary battery according to claim 12, wherein the total thickness of the second gel electrolyte is from 0.1 μm to 20 μm.

15. The bipolar secondary battery of claim 12, wherein the first gel electrolyte is impregnated throughout the separator, the positive electrode active material layer, and the negative electrode active material layer.

16. The bipolar secondary battery according to claim 12, wherein the second gel electrolyte is formed between the separator and the positive electrode active material layer and between the separator and the negative electrode active material layer.

17. The bipolar secondary battery of claim 12, wherein, based on the total pore volume of the separator, the positive electrode active material layer, and the negative electrode active material layer in the state without being impregnated with the gel electrolyte, the second gel electrolyte is further formed between the separator and the positive electrode active material layer, or between the separator and the negative electrode active material layer, corresponding to 2% to 60% of the volume.

18. The bipolar secondary battery of claim 17, wherein the thickness of the second gel electrolyte further formed between the separator and the positive electrode active material layer, or between the separator and the negative electrode active material layer, is from 0.05 μm to 20 μm.

19. A method for manufacturing a bipolar secondary battery according to claim 1, the method comprising: The first step is to form a negative electrode active material layer and a positive electrode active material layer on the two surfaces of the metal current collector to manufacture a bipolar electrode. The second step involves coating the negative electrode active material layer or the positive electrode active material layer with a composition comprising a gel-forming electrolyte and a curable multifunctional compound, and then curing it. The third step is to coat the composition forming the gel electrolyte onto at least one surface of the separator and allow it to cure. as well as The fourth step involves stacking the bipolar electrodes in multiple layers, such that the positive and negative active material layers of adjacent bipolar electrodes face each other with spacers inserted between them. The composition forming the gel electrolyte is coated with a volume larger than the total pore volume of the separator, the positive electrode active material layer, and the negative electrode active material layer.

20. The method for manufacturing a bipolar secondary battery according to claim 19, wherein the second step or the third step further comprises: The step of impregnating the coated gel-forming electrolyte composition into the negative electrode active material layer, the positive electrode active material layer, or the separator between coating the composition with the gel-forming electrolyte and curing the composition with the gel-forming electrolyte.

21. The method for manufacturing a bipolar secondary battery according to claim 20, wherein the impregnation step comprises: The step of rolling the surface of the negative electrode active material layer, the positive electrode active material layer, or the separator coated with the composition forming the gel electrolyte.

Citation Information

Patent Citations

  • A system for integrated management of apartment communities

    KR1020250025906A

  • laminate, image display device

    KR1020250136349A

  • Formulations for and methods of fabricating energy storage device electrodes

    US10153096B2

  • Dry-particle based adhesive and dry film and methods of making same

    US8815443B2